The study on relationship between technology acceptances model toward employee motivation using technology / Nur Syafiqah Alias - Alias, Nur Syafiqah (Faculty of Business and Management, 2018)
The importance of using a technology in the workplace allows businesses to expand quickly and efficiently hence, technology cannot be effective unless they are used. In this study, the researcher focus to study on relationship between Technology Acceptance Model (TAM) toward employees' motivation in Manjung Municipal Council (MMC). Questionnaires were given to 60 respondents that selected randomly from MMC employees' list names. The data was collected through questionnaire distributed personally then been analyzed by using SPSS software. The descriptive statistics were employed to analyze the data and answer the research question of the study. Descriptive statistic like means, standard deviation and percentage appropriate were used to describe research questions of the study. The result demonstrated that, some TAM construct had direct and indirect effect on employees' motivation in MMC in using technology